The Comparison of the Video Game Development Process with and without the Use of Artificial Intelligence - Ivanichenko, Anton (2025)
The main goal of this bachelor thesis is to compare the processes of video game development with and without the use of artificial intelligence. The output of this work is a comparative analysis of two game prototypes: manually developed and artificially developed. The analysis focuses on three factors: time costs, financial costs, and overall quality of the prototypes. This work also inspects several other topics, such as the definition of a video game, roles in the game development team, and components.